Analisis Konsep Dan Implikasi Overmacht Dalam Konteks Hukum : Tinjauan Dari Pers Pektif Hukum Perdata - Miftahul Jennah; Emalia (JOURNAL SAINS STUDENT RESEARCH, 2023)
The purpose of this research is to find out what contract factors influence Overmacht and how the cancellation of an agreement is caused by Overmacht, which by using normative legal research methods concludes that: 1. Overmacht. overmacht / overmach is a situation that occurs after an agreement is made, which prevents the debtor from fulfilling its achievements, where the debtor cannot be blamed and does not have to bear the risk and cannot speculate at the time the agreement is made. All of this before the debtor fails to fulfill its achievements at the time the situation arises. Factors that influence overmacht, according to the Civil Code, there are 3 (three) elements that must be fulfilled for overmacht, namely: a. Failure to meet achievements; B. There is a cause that lies beyond the debtor's fault; c. The factors causing this cannot be foreseen and cannot be accounted for by the debtor. If a overmacht occurs and fulfills elements a and c, then this overmacht/overmacht is called absolute overmacht or an objective overmacht. The basis is the impossibility (impossibility) of fulfilling achievements because the object is lost/destroyed. If overmacht/overmacht occurs which fulfills elements b and c, this situation is called relative overmacht or subjective overmacht. The basis is that it is difficult to fulfill achievements because there are events that prevent the debtor from doing so. The compelling circumstances that guarantee achievement must be circumstances regarding the achievement itself, because we cannot say that there are compelling circumstances if the circumstances occur later. 2. The legal implications of overmacht, namely that the circumstances that prevent the provision of achievements are not only if it is absolutely impossible for everyone to fulfill their achievements, even if it is impossible or very difficult for the debtor himself to fulfill the achievements. The determination must be based on each case. The implication is that the debtor does not have to bear the risk in compelling circumstances, meaning that the debtor, whether based on law, agreement or according to the views prevailing in society, does not have to bear the risk. Apart from that, due to compelling circumstances, the debtor cannot predict that an event will occur that will prevent the achievement of achievements at the time the agreement is made.